Sabun Cuci Tangan Berbahan Aktif Larutan Fermentasi Kombucha Bunga Telang (Clitoria ternatea L) Sebagai Produk Bioteknologi Farmasi Dalam Menghambat Pertumbuhan Bakteri Staphylococcus capitis, Bacillus cereus, dan Pantoea dispersa - Arikha Ayu Susilowati; Rina Nurmaulawti; Firman Rezaldi (Lembaga Pengembangan Kinerja Dosen, 2023)
Pharmaceutical biotechnology products in the form of hand washing soap with an active ingredient of telang flower kombucha fermented solution have the potential to inhibit the growth of Staphylococcus capitis, Bacillus cereus, and Pantoea dispersa bacteria. The aim of this study was to formulate and prepare hand washing soap with an active ingredient in a solution of seagrass kombucha fermentation to inhibit the growth of Staphylococcus capitis, Bacillus cereus, and Pantoea dispersa. This research is an experimental laboratory by making 4 hand washing soap preparations, which consist of a hand washing soap base without an active substance. Hand washing soap base added to a solution of fermented butterfly pea flower kombucha at a sugar concentration of 20%, 30%, and 40%. Disc diffusion is a method used to calculate the average diameter of the inhibition zone for the three tested bacterial growth. The research data obtained were analyzed through one way ANOVA and post hoc analysis. The results of the ANOVA test proved that the obtained p value <0.05, which means that there were significant differences in the three treatment groups in inhibiting the growth of the three test bacteria. The post hoc analysis results also proved that 40% concentration was the best concentration in inhibiting the growth of the three tested bacteria, namely 18.34 mm (S. capitis/strong), 16.39 mm (B. cereus/strong), and 13.33 mm (P. disperse/strong).